Certain Subclass of Multivalently Bazilevič and Non-Bazilevič Functions Involving the Lemniscate of Bernoulli (European Journal of Pure and Applied Mathematics, 2025)
Making use of the principle of subordination, we define a certain subclass of p-valently Bazilevič and non-Bazilevič functionsassociated with the Lemniscate of Bernoulli. Also, subordination results, inclusion relationship, convolution properties, coefficients estimate and Fekete--Szegö inequalities for this subclass are derived.
Keywords: Analytic functions; subordination; convolution; Fekete--Szegö problem.; non-Bazilevič function; Bazilevič function